2016
DOI: 10.1016/j.foodchem.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buffer additives and thermal processing methods on the solubility of shrimp (Penaeus monodon) proteins and the immunoreactivity of its major allergen

Abstract: This study examines the potential of two buffer additives (Tween 20 and DTT) to improve the solubility of proteins from shrimp subjected to different heat treatments and the allergenicity of tropomyosin in the extracts. The concentration of soluble proteins extracted by all the buffers from processed shrimp was significantly reduced compared with untreated samples. The concentration of total soluble proteins from heat treated shrimp increased significantly when phosphate buffer containing both surfactant and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 38 publications
7
37
0
1
Order By: Relevance
“…Because of the threat that allergens pose to human health, many scientists have been working on strategies to reduce allergenicity, including physical methods, such as heat processing (Lasekan & Nayak, 2016), irritation (Lemon-Mulé et al, 2008;Liu et al, 2017), and ultra-high pressure (Liang, Xu, Pan, Ge, & Zong, 2015); chemical methods, such as the Maillard reaction (Li, Jiang, You, Luo, & Feng, 2014;Li, Offengenden, Fentabil, Gänzle, & Wu, 2013), and enzymatic hydrolysis (Mine, 1995), and biological methods, such as traditional fermentation (Moon & Song, 2001), or gene silencing (KovacsNolan, Phillips, & Mine, 2005;Nicolai & Durand, 2013). These methods have diverse effects on allergens based on different principles, even leading to the formation of new allergenic compounds via the Maillard reaction (Rahaman, Vasiljevic, & Ramchandran, 2016;Yu, Goktepe, & Ahmedna, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the threat that allergens pose to human health, many scientists have been working on strategies to reduce allergenicity, including physical methods, such as heat processing (Lasekan & Nayak, 2016), irritation (Lemon-Mulé et al, 2008;Liu et al, 2017), and ultra-high pressure (Liang, Xu, Pan, Ge, & Zong, 2015); chemical methods, such as the Maillard reaction (Li, Jiang, You, Luo, & Feng, 2014;Li, Offengenden, Fentabil, Gänzle, & Wu, 2013), and enzymatic hydrolysis (Mine, 1995), and biological methods, such as traditional fermentation (Moon & Song, 2001), or gene silencing (KovacsNolan, Phillips, & Mine, 2005;Nicolai & Durand, 2013). These methods have diverse effects on allergens based on different principles, even leading to the formation of new allergenic compounds via the Maillard reaction (Rahaman, Vasiljevic, & Ramchandran, 2016;Yu, Goktepe, & Ahmedna, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to allergenic TPMs, the investigation showed that heating of shellfish meat enhanced recognition of multiple protein variants in the analyzed shellfish species, pointing to a possible alteration of the protein allergenic potential with this method of fish-meat treatment [81]. In contrast, evidence from protein profiling indicated that high-pressure steaming leads to protein degradation and reduces the levels of TPM in shrimp ( Penaeus monodon ), and consequently reduces the allergenicity in shrimp meat [85]. Not much is actually known with regard to the structure of the reported PRVB isoforms or TPM variants in fish and crustaceans or the structural/conformational differences that mediate the reactivity to IgEs.…”
Section: Top-down Proteomics In Aquatic Sciencesmentioning
confidence: 99%
“…However, they are also responsible for some cases of allergic reaction especially among the adult population . In the United States, the prevalence of crustacean shellfish allergy among the adult population and young children is about 2 and 0.1% respectively . Ingestion of crustacean shellfish by allergic consumers can cause serious adverse reactions including anaphylaxis .…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of crustacean shellfish by allergic consumers can cause serious adverse reactions including anaphylaxis . Consequently, crustacean shellfish is one of the ‘big 8’ food allergens that must be declared on packaged product labels …”
Section: Introductionmentioning
confidence: 99%